A Mild Dihydrobenzooxaphosphole Oxazoline/Iridium Catalytic System for Asymmetric Hydrogenation of Unfunctionalized Dialins1. (10th November 2014) - Qu, Bo; Samankumara, Lalith P.; Ma, Shengli; Fandrick, Keith R.; Desrosiers, Jean‐Nicolas; Rodriguez, Sonia; Li, Zhibin; Haddad, Nizar; Han, Zhengxu S.; McKellop, Keith; Pennino, Scott; Grinberg, Nelu; et al.
Abstract Air‐stable P‐chiral dihydrobenzooxaphosphole oxazoline ligands were designed and synthesized. When they were used in the iridium‐catalyzed asymmetric hydrogenation of unfunctionalized 1‐aryl‐3, 4‐dihydronaphthalenes under one atmosphere pressure of H2, up to 99:1 e.r. was obtained. High enantioselectivities were also observed in the reduction of the exocyclic imine derivatives of 1‐tetralones.